CXCL16 deficiency attenuates acetaminophen-induced hepatotoxicity through decreasing hepatic oxidative stress and inflammation in mice. (28th April 2017) - Wang, Hong; Shao, Yihui; Zhang, Saisai; Xie, Anqi; Ye, Yanna; Shi, Lihua; Jin, Leigang; Pan, Xuebo; Lin, Zhuofeng; Li, Xiaokun; Yang, Shulin
Abstract: Chemokine C-X-C ligand 16 (CXCL16), a single-pass Type I membrane protein belonging to the CXC chemokine family, is related to the inflammatory response in liver injury. In present study, we investigated the pathophysiological role of CXCL16, a unique membrane-bound chemokine, in acetaminophen (APAP)-induced hepatotoxicity in mice. Mice were injected with APAP, and blood and tissue samples were harvested at different time points. The serum high-mobility group box 1 and CXCL16 levels were quantified by sandwich immunoassays. The liver tissue sections were stained with hematoxylin-eosin or with dihydroethidium staining. The expressions of CXCL16 and other cytokines were examined by real-time polymerase chain reaction. Ly6-B, p-jun N-terminal kinase (p-JNK), and JNK expressions were measured by western blot analysis. Intracellular glutathione, reactive oxygen species, and malondialdehyde levels were also measured. APAP overdose increased hepatic CXCL16 mRNA and serum CXCL16 protein levels. CXCL16-deficient mice exhibited significantly less liver injury and hepatic necrosis, as well as a lower mortality than wild-type (WT) mice in response to APAP-overdose treatment. APAP elevated the production of oxidative stress and decreased mitochondrial respiratory chain activation in WT mice, which was strongly reversed in CXCL16-knockout mice. In addition, CXCL16 deficiency inhibited the neutrophil infiltration and the production of proinflammatory cytokines triggered by APAP-overdose treatment. Our study revealed that CXCL16 is a critical regulator of liver immune response to APAP-induced hepatotoxicity, thus providing a potential strategy for the treatment of drug-induced acute liver failure by targeting CXCL16.